2018
DOI: 10.1017/s1755691018000579
|View full text |Cite
|
Sign up to set email alerts
|

A morphological revision of Keraterpeton, the earliest horned nectridean from the Pennsylvanian of England and Ireland

Abstract: The aquatic diplocaulid nectridean Keraterpeton galvani is the commonest taxon represented in the Jarrow Coal assemblage from Kilkenny, Ireland. The Jarrow locality has yielded the earliest known Carboniferous coal-swamp fauna in the fossil record and is, therefore, of importance in understanding the history and diversity of the diplocaulid clade. The morphology of Keraterpeton is described in detail with emphasis on newly observed anatomical features. A reconstruction of the palate includes the presence of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…If the identification of the putative ilium in TCD.T87 is correct, then I. bradleyae had a unipartite dorsal iliac process, which is also seen in colosteids (Godfrey, 1989), nectrideans (Milner, 2019), and Aytonerpeton (Clack et al, 2016). However, in these three taxa, the dorsal process curves more posteriorly and is square-ended at its apex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the identification of the putative ilium in TCD.T87 is correct, then I. bradleyae had a unipartite dorsal iliac process, which is also seen in colosteids (Godfrey, 1989), nectrideans (Milner, 2019), and Aytonerpeton (Clack et al, 2016). However, in these three taxa, the dorsal process curves more posteriorly and is square-ended at its apex.…”
Section: Discussionmentioning
confidence: 99%
“…Clack et al (2019) identified a clade of stem tetrapods consisting of taxa with long bodies and reduced limbs (colosteids and nectrideans) or lacking limbs (aïstopods, adelospondyls, and Acherontiscus ). Vertebral arrangement is diverse within this clade, which includes rhachitomous vertebrae (colosteids: Hook, 1983; Godfrey, 1989), diplospondylous amphicoelous vertebrae ( Acherontiscus : Carroll, 1969; Clack et al, 2019), monospondylous vertebrae with sutured neural arches (adelospondyls: Andrews and Carroll, 1991), and holospondylous vertebrae (aïstopods and nectrideans [Anderson, 2002, 2003; Milner, 2019]). When present, the iliac process is unipartite in this clade, seen in colosteids (Godfrey, 1989), nectrideans (Milner, 2019), and Aytonerpeton (Clack et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among Paleozoic tetrapods, tetradactyly is only known among “microsaurs” (including lysorophians), scincosaurids, some urocordylids, temnospondyls, and Colosteus (but not its close pentadactyl relative Greererpeton ). (Reports of tetradactyl limbs in diplocaulids have been erroneous: Marjanović and Laurin, 2019 ; Milner, 2019 , and references therein.) Colosteus and probably ( Clack et al, 2019 ) the urocordylids are stem-stegocephalians, but both were fully aquatic, thus unlikely to leave trackways; “microsaurs” and probably scincosaurids were tetrapods, and most were amphibious to terrestrial; temnospondyls spanned the full range of lifestyles, but see above for their phylogenetic position.…”
Section: Methodsmentioning
confidence: 99%
“…Among Paleozoic tetrapods, tetradactyly is only known among “microsaurs” (including lysorophians), scincosaurids, some urocordylids, temnospondyls and Colosteus (but not its close pentadactyl relative Greererpeton ). (Reports of tetradactyl limbs in diplocaulids have been erroneous: Milner, 2019; Marjanović and Laurin, 2019, and references therein.) Colosteus and probably (Clack et al, 2019) the urocordylids are stem-stegocephalians, but both were fully aquatic, thus unlikely to leave trackways; “microsaurs” and probably scincosaurids were tetrapods, and most were amphibious to terrestrial; temnospondyls spanned the full range of lifestyles, but see above for their phylogenetic position.…”
Section: Methodsmentioning
confidence: 99%